Integrated analysis of the chemical-material basis and molecular mechanisms for the classic herbal formula of Lily Bulb and Rehmannia Decoction in alleviating depression - Hongxiu Zhang; Xiaoyan Xue; Jin Pan; Xiaobin Song; Xing Chang; Qiancheng Mao; Yanting Lu; Haijun Zhao; Yuan Wang; Xiansu Chi; Shijun Wang; Ke Ma (BMC, 2021)
Abstract Background Lily Bulb and Rehmannia Decoction (LBRD), is a traditional Chinese formula that has been shown to be safe and effective against depression; however, its material basis and pharmacological mechanisms remain unknown. Methods Here, ultra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS) and high-performance liquid chromatography (HPLC) were used to identify the chemical spectrum and qualitatively identify the major active ingredients in the LBRD standard decoction, respectively. Subsequently, we assessed the behavior, neuronal function and morphology, neurotransmitter levels, hypothalamic-pituitary-adrenal (HPA)-axis associated hormones, inflammatory cytokine levels, and miRNA/mRNA expression alterations in an in vitro/vivo depression model treated by the LBRD standard decoction. Finally, miRNA/mRNA regulatory networks were created through bioinformatics analysis, followed by functional experiments to verify its role in LBRD standard decoction treatment. Results A total of 32 prototype compounds were identified in the LBRD standard decoction, and the average quality of verbascoside in the fresh lily bulb decoction, fresh raw Rehmannia juice, and the LBRD standard decoction were 0.001264%, 0.002767%, and 0.009046% (w/w), respectively. Administration of the LBRD standard decoction ameliorated chronic unpredictable mild stress (CUMS)-induced depression-like phenotypes and protected PC12 cells against chronic corticosterone (CORT)-induced injury. The levels of neurotransmitter, cytokine, stress hormones and neuronal morphology were disrupted in the depression model, while LBRD standard decoction could work on these alterations. After LBRD standard decoction administration, four differentially expressed miRNAs, rno-miR-144-3p, rno-miR-495, rno-miR-34c-5p, and rno-miR-24-3p, and six differentially expressed mRNAs, Calml4, Ntrk2, VGAT, Gad1, Nr1d1, and Bdnf overlapped in the in vivo/vitro depression model. Among them, miR-144-3p directly mediated GABA synthesis and release by targeting Gad1 and VGAT, and miR-495 negatively regulated BDNF expression. The LBRD standard decoction can reverse the above miRNA/mRNA network-mediated GABA and BDNF expression in the in vivo/vitro depression model. Conclusion Collectively, the multi-components of the LBRD standard decoction altered a series of miRNAs in depression through mediating GABAergic synapse, circadian rhythm, and neurotrophic signaling pathway etc., thereby abolishing inhibitory/excitatory neurotransmitter deficits, recovering the pro-/anti-inflammatory cytokine levels and regulating the HPA-axis hormone secretion to achieve balance of the physiological function of the whole body.